2015
DOI: 10.7589/2014-04-114
|View full text |Cite
|
Sign up to set email alerts
|

FELINE IMMUNODEFICIENCY VIRUS AND FELINE LEUKEMIA VIRUS INFECTION IN FREE-RANGING GUIGNAS (LEOPARDUS GUIGNA) AND SYMPATRIC DOMESTIC CATS IN HUMAN PERTURBED LANDSCAPES ON CHILOÉ ISLAND, CHILE

Abstract: Feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) are two of the most common viruses affecting domestic cats (Felis catus). During the last two decades, reports show that both viruses also infect or affect other species of the family Felidae. Human landscape perturbation is one of the main causes of emerging diseases in wild animals, facilitating contact and transmission of pathogens between domestic and wild animals. We investigated FIV and FeLV infection in free-ranging guignas (Leopardus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 32 publications
3
39
0
2
Order By: Relevance
“…Can the risk of zoonotic infection with FeLV be discounted? Despite control measures, including vaccination, that have reduced the prevalence of FeLV in some parts of the world, this virus family remains one of the most important pathogens of cat species worldwide ( 52 ). Moreover, the limited barriers protecting human cells against FeLV infection contrast with the plethora of restriction factors that protect against the cross-species transmission of primate lentiviruses, where recent jumps have occurred ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Can the risk of zoonotic infection with FeLV be discounted? Despite control measures, including vaccination, that have reduced the prevalence of FeLV in some parts of the world, this virus family remains one of the most important pathogens of cat species worldwide ( 52 ). Moreover, the limited barriers protecting human cells against FeLV infection contrast with the plethora of restriction factors that protect against the cross-species transmission of primate lentiviruses, where recent jumps have occurred ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on a Chilean island found a prevalence of infection, by PCR, for FeLV of 33% (26/78) (Mora et al 2015) [EB1]. Seroprevalence of retroviral exposure in a cross-sectional survey of a convenience sample of domestic cats from Costa Rica's greater metropolitan area was 16.7% (17/102) for FeLV and 8.8% (9/102) for FIV (Blanco et al 2009) [EB1].…”
Section: Feline Retrovirusesmentioning
confidence: 99%
“…Mora y cols. (2015), documentan que las guiñas en Chiloé se encuentran infectadas con los virus de la leucemia felina (VLFe) y de la inmunodeficiencia felina (VIF) sin signos clínicos aparentes 85 . Las secuencias nucleotídicas obtenidas de ambos virus en guiñas fueron casi idénticas a aquellas presentes en gatos domésticos, sugiriendo que estos pueden estar jugando un rol importante en la transmisión de retrovirus a los felinos silvestres.…”
Section: Patógenos Y Mamíferos Silvestres Desatendidosunclassified